Immunity and physiological changes in adult honey bees (Apis mellifera) infected with Nosema ceranae: The natural colony environment. (May 2021) - Lourenço, Anete P.; Guidugli-Lazzarini, Karina R.; de Freitas, Nayara H.A.; Message, Dejair; Bitondi, Márcia M.G.; Simões, Zilá L.P.; Teixeira, Érica W.
Graphical abstract: Highlights: Nosema ceranae immunosuppressed honey bees in the colony context on the field. The colony context lowered Nosema ceranae load. Nosema ceranae infection promoted dysregulation of immune related mRNAs, protein, and miRNAs. Abstract: Nosema ceranae is a microsporidium that infects Apis mellifera, causing diverse physiological and behavioral alterations. Given the existence of individual and social mechanisms to reduce infection and fungal spread in the colony, bees may respond differently to infection depending on their rearing conditions. In this study, we investigated the effect of N. ceranae in honey bee foragers naturally infected with different fungal loads in a tropical region. In addition, we explored the effects of N. ceranae artificially infected young bees placed in a healthy colony under field conditions. Honey bees naturally infected with higher loads of N. ceranae showed downregulation of genes from Toll and IMD immune pathways and antimicrobial peptide (AMP) genes, but hemolymph total protein amount and Vitellogenin (Vg) titers were not affected. Artificially infected bees spread N. ceranae to the controls in the colony, but fungal loads were generally lower than those observed in cages, probably because of social immunity. Although no significant changes in mRNA levels of AMP-encoding were observed, N. ceranae artificially infected bees showed downregulation of miR-989 (an immune-related microRNA), lower vitellogenin gene expression, and decreased hemolymph Vg titers. Our results demonstrate for the first time that natural infection by N. ceranae suppresses the immune system of honey bee foragers in the field. This parasite is detrimental to the immune system of young and old bees, and disease spread, mitigation and containment will depend on the colony environment.